1999
DOI: 10.1007/s002109900043
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic cannabinoid and imidazoline receptors in the human heart and their potential relationship

Abstract: Segments of human right atrial appendages preincubated with [3H]noradrenaline and superfused with physiological salt solution containing desipramine and corticosterone were used to examine whether the cardiac sympathetic nerves are endowed with cannabinoid receptors and to further study pharmacological properties of presynaptic imidazoline receptors. The cannabinoid CB1 receptor agonists CP55,940, HU210 and anandamide inhibited evoked [3H]noradrenaline release. The inhibition by CP55,940 and anandamide was abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 20 publications
0
38
0
2
Order By: Relevance
“…These putative receptors have been reported to be activated by CP55940 (300 nM) and R-(ϩ)-WIN55212 (10 and 100 M) but not by anandamide (1 M) and to be blocked by rimonabant (1 M) and LY320135 (0.1 to 10 M) (Molderings et al, 1999.…”
Section: H Some Putative Receptorsmentioning
confidence: 99%
“…These putative receptors have been reported to be activated by CP55940 (300 nM) and R-(ϩ)-WIN55212 (10 and 100 M) but not by anandamide (1 M) and to be blocked by rimonabant (1 M) and LY320135 (0.1 to 10 M) (Molderings et al, 1999.…”
Section: H Some Putative Receptorsmentioning
confidence: 99%
“…This phenomenon may even have a prognostic relevance because CB 1 blockade decreased the survival rate. Functional presynaptic inhibitory CB 1 receptors sensitive to AEA have also been identified in human heart (Molderings et al, 1999). Further studies are necessary to clarify whether drug therapies directed against presynaptic inhibitory CB 1 receptors are effective in myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, investigations by other authors revealed that these drugs inhibit noradrenaline release exclusively by activating prejunctional ␣ 2 -adrenoceptors (Bohmann et al, 1994;Gaiser et al, 1999). Whether imidazoline binding sites are involved (in addition to ␣ 2 -adrenoceptors) in noradrenaline release may be dependent on stimulation conditions (Molderings et al, 1999a) and/or species differences (Molderings et al, 2000).…”
mentioning
confidence: 88%